THE NEXUS BETWEEN LIVELIHOOD DIVERSIFICATION AND NUTRITION SECURITY AMONG FARMING HOUSEHOLDS IN NIGERIA (FUDMA JOURNAL OF SCIENCES, 2025)
In a country where millions of farming household heads struggle to feed their families in the face of economics hardship, the need to diversify income sources becomes inevitable. This study therefore examined the determinants of livelihood diversification among farming households in Nigeria. Using secondary data from the generalized household survey (GHS) 2018/2019 wave 4, this study investigated the relationship between nutrition security and livelihood diversification among farming households in Nigeria. The data was analyzed using descriptive statistics, nutrient adequacy ratio (NAR), and two stage least square regression model. Results from the computed mean adequacy ratio (MAR) showed that 54% of the farming households were found to be nutrition insecure, while 46% were nutrition secure. The profiling of nutrition security status of the farming households showed that majority of farming households were nutritional insecure. The mapping also indicated that farming households in North central, Northwest, South-south and Southwest were more nutrition secure than farming households in the Northeast and Southeast. The two stage least square (2SLS) regression result revealed that age had a substantial negative impact on nutrition security, while sex, education, household size, and livelihood diversification had favourable positive significant effects. The study therefore conclude that a strong and favourable correlation exist between nutrition security and livelihood diversification. The study recommends the need to improve nutrition security in Nigeria through nutrition education and sensitization programs on dietary diversity and micronutrient adequacy as well as enlightening of farmers on the need to consume more of foods that are rich in micronutrients.
Keywords: Livelihood diversification; Nutrition security; Nutrient Adequacy Ratio; Herfindahl index; Nigeria